T, I, O, O, S, P, A, C, E, N, S The Influence of Online Sales Promotion and Celebrity Endorser Nagita Slavina on the Brand Image of Toko Mama Gigi - Chairunisa, Dinda; Sudradjat, Ratih Hasanah (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
Advances in technology and the internet make it easier for businesses to innovate in the promotion and delivery of information. Mama Gigi's store uses online sales promotion through Shopee live shopping and celebrity endorser Nagita Slavina to build a brand image. This study, which used Houland's S-O-R theory and quantitative methods with 400 respondents, found that online sales promotion and celebrity endorsers had a positive and significant effect on Toko Mama Gigi's brand image, with an influence of 46.9%, while 53.1% was influenced by other factors that were not studied.